The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/000313481508101226
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Ostomy Site Incisional Hernias after Stoma Closure

Abstract: This study sought to evaluate the incidence of ostomy site incisional hernias after stoma reversal at a single institution. This is a retrospective analysis from 2001 to 2011 evaluating the following demographics: age, gender, indication for stoma, urgent versus elective operation, time to closure, total follow-up time, the incidence of and reoperation for stoma incisional hernia, diabetes, postoperative wound infection, smoking status within six months of surgery, body mass index, and any immunosuppressive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…The effects of hypertension on wound healing are less clear; possibly chronic microvascular changes secondary to hypertension could impair adequate tissue perfusion, thereby reducing proper wound healing and contributing to possible wound dehiscence. It is likely that other factors identified in previous studies, such as diabetes mellitus and wound infection, are also independent risk factors for hernia development. The low incidence of these factors in the present study might explain why they were not identified.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The effects of hypertension on wound healing are less clear; possibly chronic microvascular changes secondary to hypertension could impair adequate tissue perfusion, thereby reducing proper wound healing and contributing to possible wound dehiscence. It is likely that other factors identified in previous studies, such as diabetes mellitus and wound infection, are also independent risk factors for hernia development. The low incidence of these factors in the present study might explain why they were not identified.…”
Section: Discussionmentioning
confidence: 54%
“…Several previous studies have looked at possible risk factors for incisional hernia following stoma reversal. High BMI and having a temporary colostomy were identified as significant risk factors in several of these studies , . Parastomal hernia, stoma prolapse and hypertension have not been identified previously; most of these factors were not included in other studies.…”
Section: Discussionmentioning
confidence: 98%
“…The reasons for the large variations may be multifactorial. Many of the studies include both small and large bowel ostomies [11,12,[15][16][17]. Hernias may be more common after reversal of large bowel ostomies principally because of the larger size of the abdominal wall defect.…”
Section: Discussionmentioning
confidence: 99%
“…High BMI and male sex were significant risk factors in this study. BMI has been shown to be a risk factor in many other studies [12,13,17,18] and is a factor to consider when choosing a technique for the reversal of the ostomy. Other studies have found female sex to be a risk factor for recurrence after incisional hernia repair [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation